Social Isolation and Its Impact on the Health Status of Older People in the Community: A Narrative Review - Suyasa, I Gede Putu Darma (Babali Nursing Research, 2025)
Introduction: Older people often face multifaceted challenges encompassing physical, psychological, and social dimensions. Among these, social isolation is a significant concern, frequently resulting from age-related degenerative changes, the loss of loved ones, or abandonment by family members. Numerous studies have indicated that social isolation can adversely affect the health and well-being of older people. However, comprehensive syntheses of recent research examining the impact of social isolation on the health status of community-dwelling older people remain limited and insufficiently explored. This study aimed to identify and summarize the latest findings regarding social isolation's impact on older people's health status.Methods: This narrative review design used databases PubMed, Science Direct, and EBSCOhost. Keywords include "social isolation" OR "loneliness" AND "older people". Literature selection was carried out non-systematically and analyzed descriptively.Results: Our search found 87 articles; 11 met the inclusion criteria. Most studies were from China (4), the United States (3), and others from England, Brazil, and Colombia. Key finddings indicated that older people living with social isolation have a high risk of depression, cognitive decline, dementia, Alzheimer's disease, changes in biochemical parameters in blood glucose and triglycerides, physical weakness and disability, difficulties in ADL and IADL, disorders, low self-assessment of health, risk of falls, low utilization of health care facilities, poor emotional well-being, and higher risk of death.Conclusion: Social isolation has been shown to have a very negative impact on the health status of older people. Community nurses need to enhance the implementation of home visit programs to support socially isolated older people better. Future research should focus on conducting longitudinal and intervention-based studies to investigate the causal relationships between social isolation and health outcomes.